Some overdetermined problems for the fractional Laplacian equation on the exterior domain and the annular domain. (July 2016) - Li, Dongsheng; Li, Zhenjie
Abstract: In this paper, by the method of moving planes, we extend the Serrin-type overdetermined problem to the fractional Laplacian equation on the exterior set of a multiply connected domain and the annular domain.